Analisis Pengaruh Kavitasi pada Pompa Sentrifugal Graving Dock - Al Farrel Ghazali; Emie Santoso (Politeknik Perkapalan Negeri Surabaya, 2023)
Centrifugal pump at the graving dock experienced cavitation. It caused noise and a damage to its impeller as vapor bubbles appeared around it. This problem caused the centrifugal pump’s power decreased. The research method to solve it is collecting, calculating, and analyzing data. The calculations analyzed are the calculation of velocity, friction factor, head losses, pump head, NPSHA and NPSHR values. If NPSHA value is less than NPSHR, the pump is cavitated and modification to the piping system is needed so that the cavitation problem can be overcomed. The NPSHA calculation result is 4.77 m while the NPSHR is 6 m so that the it can be concluded that the pump experienced cavitation. Based on these calculations, modification of its centrifugal pump piping system is required. The pump which was originally had a suction pipe length of 6 meters was shortened to 5 meters. The pump position was lowered so that the suction pipe could reach the lowest water level at the graving dock. The pipe diameter of 0.3 meters was enlarged to 0.4 meters. After modification, the NPSHA value exceeds the NPSHR by 0.7 meters so that the centrifugal pump will be safe from cavitation.